(untitled) (Tidsskrift for Praktisk Teologi, 2020)
The article first identifies and explicates three research areas as central to Nordic practical-theological research in ecclesiology: studies of local congregations, of statechurch – relations, and of processes of change and reform. In dialogue with these three research areas, it reflects on fundamental features pertaining to an empirically oriented contemporary practical-theological ecclesiology: First its origin within as well as close collaboration and porous interface with other disciplines, especially social sciences – and the implications for understanding practical-theological ecclesiology as a theological discipline. Second, how practical-theological ecclesiology studies and explicates “church” as a social reality along three different dimensions: as interaction, institution and organization, evoking the question about the relation between these three perspectives. And third, how empirically oriented practical-theological ecclesiology also challenges and destabilizes “church” as a social and concrete phenomenon and area of research.